2016
DOI: 10.1371/journal.pone.0167881
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Ecological Variables Associated with Context-Specific Sitting Time in Belgian Older Adults: A One-Year Follow-Up Study

Abstract: IntroductionKnowledge about variables associated with context-specific sitting time in older adults is limited. Therefore, this study explored cross-sectional and longitudinal associations of socio-demographic, social-cognitive, physical-environmental and health-related variables with sitting during TV viewing, computer use and motorized transport in older adults.MethodsA sample of Belgian older adults completed structured interviews on context-specific sitting time and associated variables using a longitudina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 49 publications
(70 reference statements)
0
12
1
Order By: Relevance
“…The current study aims to understand (1) whether home environmental factors are related to (older) adults’ domain-specific sedentary behaviors; and (2) whether these associations are moderated by socio-demographic variables and BMI. In contrast to the findings of the earlier studies of Busschaert et al [ 16 , 17 ], our regression analyses revealed multiple significant associations between the included home environmental factors and domain-specific sedentary behaviors, especially in healthy weight adults. Nevertheless, the direction of the associations remains unclear as the included environmental factors are related to adults’ immediate environment, and adults are having control over it.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The current study aims to understand (1) whether home environmental factors are related to (older) adults’ domain-specific sedentary behaviors; and (2) whether these associations are moderated by socio-demographic variables and BMI. In contrast to the findings of the earlier studies of Busschaert et al [ 16 , 17 ], our regression analyses revealed multiple significant associations between the included home environmental factors and domain-specific sedentary behaviors, especially in healthy weight adults. Nevertheless, the direction of the associations remains unclear as the included environmental factors are related to adults’ immediate environment, and adults are having control over it.…”
Section: Discussioncontrasting
confidence: 99%
“…For the present study, cross-sectional survey data were collected as part of the Busschaert study [ 16 , 17 ] to determine correlates of sedentary behaviors in adults (25–60 years) and older adults (≥65 years).…”
Section: Methodsmentioning
confidence: 99%
“…This study used cross-sectional survey data, collected between April 2013 and May 2014 as part of the Busschaert study. The Busschaert study was designed to determine correlates of sedentary behaviors in adolescents (12–18 years) [ 31 ], adults (25–60 years) [ 32 ] and seniors (>65 years) [ 33 ]. Details on the study protocol, which was approved by the Ethics Committee of Ghent University Hospital (B670201317406), have been published elsewhere [ 31 , 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…The rst study was the Belgian Environmental Physical Activity Study in Seniors (BEPAS Seniors) that was conducted between 2010 and 2012, and aimed to gain insight into the physical environmental correlates of older adults' activity-related behaviors (27). The second study was conducted by Busschaert and colleagues, in 2013, to examine socio-ecological correlates of older adults' domainspeci c sedentary behavior (28). Both studies were approved by the Ethics Committee of the Ghent University Hospital (B670201423000 and B670201317406, respectively) and all participants provided written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…The public service of Sint-Niklaas (i.e. city in Flanders, Belgium) randomly selected 961 independently living older adults (≥ 65 years) from the municipal register (28). Selected older adults received an information letter by postal mail describing the background, objectives, and practical information of the study.…”
Section: Recruitment and Participantsmentioning
confidence: 99%